The Fiber-Optic Gyroscope, Third Edition - Lefevre, Herve C. (Artech House, 2022)
This landmark work - considered by many in the field to be THE reference on fiber-optic gyroscopes (FOGs) - provides you with a complete and thorough system analysis of the FOG and remains unmatched by any other single source.Now in its third edition, this fully updated and authoritative book:Gives you access to all the details you need to know about optics, single-mode fiber optics, and integrated optics to fully grasp the design rules of the fiber-optic gyroscope; Helps you understand the concepts that have emerged as the preferred solutions to obtain a practical device; Guides you through the advances that have occurred in the last seven years since the previous edition was published and how they are implemented in the current FOGs. Drawing on 45 years of research and development, The Fiber-Optic Gyroscope, Third Edition, features new content on the relationship between white-noise power spectral density and random walk; Allan variance; testing with optical coherence domain polarimetry; a new simple mechanical model of the thermally induced stresses and related strains in the sensing coil; simple viewing of the reduction of the Shupe effect with symmetrical windings; and comments about dispersion and birefringence dispersion. The book contains over 350 illustrations (including 70 new figures) and many helpful appendixes, and gives you everything you need to understand the fiber gyro.The author is a leading expert in this field and is one of the early pioneers of the practical optical architecture and signal processing technique that is universally used in today#x92;s FOGs.This is a must-have reference for anyone working with FOGs, from students and academics learning about the device, to optoelectronics engineers and professionals needing to stay abreast of the current concepts and recent advances.